Study of Antioxidant and Membrane Resistant Peculiarities of a New Cyan Containing Lactone in Membranes of Hepatocytes with Sarcoma-45 - G.M.Galoyan,; P.A.Ghazaryan, (Journal of Enzymes, 2020)
The antioxidant and membrane resistant peculiarities of a new derivative (2-cyan-3,4,4-trymethil-2-buten-4-olyd - CTBO) of cyan containing unsaturated lactones have been studied in membranes of hepatocytes with Sarcoma-45 1. The results of our previous research 123 showed significant changes of phospholipid (PL) exchange in hepatocytes of microsomal membranes at experimental animals vaccinated with Sarcoma-45 tumor strain. It is manifested in significant changes of quantitative and qualitative contents of membrane phospholipids separate fractions, increase of cytotoxic lysophospholipids (LPCs), phosphatidylinositol (PI) and phosphatidic acid (PA) levels, significant decrease of phosphatitylcholines (PC) and sphingomyeline (SP) contents, statistically significant changes of PL/PL ratio, peroxidation ratio intensity, dramatic increase of phospholipase A2 (PLA2)activity, quantitative and qualitative changes of adenyl nucleotides, as well as disorders of adenosine triphosphatase (ATPase) system activity 34567.
Keywords: cyan containing lactone; sarcoma-45; hepatocytes; phospholipids; lipid peroxidation; metalloproteins